2007
DOI: 10.1002/ijc.22284
|View full text |Cite
|
Sign up to set email alerts
|

Reply to the letter to the editor

Abstract: Reply to the letter to the editor Dear Sir,We read with great interest the Letter to the Editor by Aubertin et al. 1 in which they reported that 100% of 39 tested oral squamous cell carcinoma (OSCC) samples contained wild-type sequence in codon 697 of the FGF receptor 3 gene. These results appear to contradict our own finding that 62% of 71 tested OSCC samples possessed a somatic missense mutation, which resulted in a glycine to cysteine substitution at position 697 (G697C) of FGFR3. 2 As we also found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Moreover, CPL304110 inhibited the FGFR3 variant with activating G697C mutation that was observed in 62% (44/71) of the examined oral squamous cell carcinoma (OSCC). It is possible that the activating potential of this mutation could be context-dependent and may involve interaction with other genes (7,9).…”
Section: Popiel Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, CPL304110 inhibited the FGFR3 variant with activating G697C mutation that was observed in 62% (44/71) of the examined oral squamous cell carcinoma (OSCC). It is possible that the activating potential of this mutation could be context-dependent and may involve interaction with other genes (7,9).…”
Section: Popiel Et Almentioning
confidence: 99%
“…Multiple studies have already shown that activation of the FGFR signaling cascade is involved in the proliferation of tumor cells (7)(8)(9)11). Thus, the antiproliferative activity of CPL304110 was determined in a panel of human tumor cell lines of different origins that are dependent on FGFR signaling.…”
Section: Cpl304110 Inhibits the Proliferation Of Fgfr-dependent Cance...mentioning
confidence: 99%
See 1 more Smart Citation